Повышение конкурентоспособности предприятия как условие его стабильного развития - Лысенко (Звёздочкина), Елена Анатольевна (My University, 2017)
В работе проведен анализ условий проведения оптимизации бизнес-процессов предприятия. Выявлено оптимальные пути реализации основной стратегии стабильного развития предприятия в современной рыночной среде. The analysis of conditions of carrying out of optimization of business processes of the enterprise is carried out in paper. The optimal ways of realization of the basic strategy of stable development of the enterprise in the modern market environment are revealed.
Keywords: кафедра економіки праці та менеджменту; конкуренция; бизнес-процесс; оптимизация; competition; business process; optimization